Alleviating the Challenges with Remote Learning during a Pandemic - Hani Morgan (MDPI AG, 2022)
The COVID-19 pandemic has caused many challenges that resulted from the suspension of face-to-face classes. Some of these challenges involved the problems associated with remote learning. One problem with this approach to learning is that it can be didactic. Remote learning can contribute to loneliness as well, and the lack of access to reliable technological resources that many students from low-income families experience can contribute to learning setbacks. Although the pandemic has created challenges related to providing remote learning opportunities and keeping students emotionally and physically healthy, some schools and colleges have used various methods to alleviate these concerns. This study focuses on the challenges associated with remote learning when it is implemented during the suspension of face-to-face classes. It also explores the practices that can be used to alleviate the obstacles that may cause students to experience setbacks.